Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Equity Pada PT Arwana Citramulia Tbk Periode 2012 - 2021 - Yuel Wijaya; Dhaniel Hutagalung; Whan Augustin Ainul Amri; Tiardo Jonathan Marusaha (Soratekno Publisher, 2025)
This study aims to determine the partial and simultaneous effects of the Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Equity (ROE) at PT Arwana Citramulia Tbk. over a 10-year period from 2012 to 2021. This research is associative in nature, with sample selection using a purposive sampling technique. The type of data used is quantitative, obtained from the company's audited financial statements, totaling 40 data points from the 2012-2021 period. The data source used in this study is secondary, obtained from the official website of the Indonesia Stock Exchange. Data processing was conducted using the statistical program IBM SPSS version 22. The data analysis techniques employed include statistical tests such as classical assumption tests, simple and multiple regression tests, coefficient of determination (R²) test, T-test, and F-test. The research findings indicate that; The partial test for the Current Ratio resulted in a significance value of 0.244 > 0.05, with a comparison of t_calculated < t_table (1.186 < 2.03224), meaning there is no significant partial effect of the Current Ratio on Return on Equity. The partial test for the Debt to Equity Ratio resulted in a significance value of 0.001 < 0.05, with a comparison of t_calculated < -t_table (-3.589 < -2.03224), indicating a significant and negative partial effect of the Debt to Equity Ratio on Return on Equity. The simultaneous test for the Current Ratio and Debt to Equity Ratio resulted in a significance value of 0.004 < 0.05, with a comparison of F_calculated > F_table (6.443 > 3.28), meaning that together, the Current Ratio and Debt to Equity Ratio have a significant and positive effect on Return on Equity.